Effects of composite thickness on shear bond strength to dentin (Mustansiria Dental Journal, 2024)
Sixty non-carious extracted human molars were used in this study. The enamelon the occlusal surface ofthe crown of the tooth was removed by a diamond bur thenthe surfaces of the teeth were ground flat. The teeth were randomly divided into sixgroups each of ten and stored in distilled water at 370 C. Two types of composite wereused in this study, Definite and Tetric. The bonding agents Etch and Prime wereprepared according to manufacturers directions and applied to the dentin surface onthe first three groups and light cured for 20 seconds. The composite Definite waspacked into either 2, 3, and 4mm thick using split metal mould in the first, secondand third groups respectively and bulk-cured from top of the composite for 40seconds, the same procedure was repeated in the remaining three groups but thecomposite used was Tetric which its corssponding bonding agent was Excite. Thebond strength was measured with universal compression machine.The results showed `that there was no significant difference between the two types of composite Tetric andDefinite used in this study. The shear bond strength was affected by the compositethickness, the 2 mm increment showed higher bond strength than the 3mm and 4mmincrement in both composites